#TITLE_ALTERNATIVE# - LYSTIANINGRUM (NIM 10105049); Pembimbing: Dr. Kuntjoro Adji Sidarto, SINDY
Flexible binomial model is a modification of Cox, Ross, and Rubinstein binomial model (CRR) with a tilt parameter that alters the shape and span of the binomial tree. In pricing vanilla option, the binomial tree can be recalibrated through this tilt parameter in order to position nodes relative to the strike price of the option. The flexible binomial model gives more numerical accuracy than CRR model. This turns out an extrapolation technique that can be used to greatly enhance the rate of convergence for pricing the option. In pricing barrier option, with continuous or discrete monitoring, the binomial tree is spanned in two stages. In the first stage, by the tilt parameter, a node is put exactly on the barrier, and the second stage the tree is designed to resemble the CRR tree so that horizontal layers of nodes are present in the tree. The price of the option calculated by the flexible binomial model closes to the exact solution (Merton formula for continuous barrier option) and the approximation of the exact solution (Broadie, Glasserman, and Kou for discrete barrier option).